Some Features of a Typical House as Perceived by Native Speakers of English and of Serbian - Dilparić, Branislava M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The paper reports findings from one of the two differently-designed surveys conducted among groups of both native speakers of English and native speakers of Serbian with a common general objective to obtain a picture of better candidates for a role of the whole (to be analyzed into its constituent elements) in the contrastive study on the lexical field a house and its parts in English and Serbian. The specific objective of the survey presented here, however, was to build up the target picture with some of the features of the ideal example of the house category, such as the shape of the house, the key materials its principal structural elements (foundations, walls, a roof) are made of, the number of residential units in the house and the type of the household that occupies it, the number of the house levels, the minimum of its interior spatial components and their functions, the types of systemic parts in the house, the status and position of the house relative to surrounding buildings, etc. Also, taking into consideration that the demographic profiles of the survey participants reflected various cultural backgrounds (which significantly influence the formation of mental images of a typical sample of the category), the survey aimed to compare the similarities and differences between the “English” and the “Serbian” typical house, that is the features assigned to a typical house by most of the surveyed representatives of Anglo-American and by those of Serbian culture. Judging exclusively by the features observed and the results obtained, the study concludes that the “English” and the “Serbian” typical house look very similar in many aspect and that the two different cultures are not as distant as they may seem.